Persepsi dan Pemahaman Pelaku Usaha Terhadap Pentingnya Laporan Keuangan pada UMKM - Mohammad David Santiago; Sri Dwi Estiningrum (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study aims to see the perceptions and understanding of entrepreneurs of Micro, Small and Medium Enterprises (MSMEs) on the importance of financial reports." This research is a type of quantitative descriptive research. This study uses primary data obtained from the results of a questionnaire distributed to 70 MSME actors in the famous Tulungagung Regency in 19 Districts. The results showed that MSME actors in Tulungagung Regency have shown good perceptions as evidenced by the results of the research that on average reports are ready to prepare financial reports in a business, including to see business development, support business interests such as tax interests and the interest of applying for credit to the bank. as additional capital. Good perceptions of these students by experience or experience running a business and educational background. However, the understanding of MSME actors in Tulungagung still needs to be improved because there are still business actors in Tulungagung who do not see how to prepare financial reports according to standards that support them to help financial reports, this is due to the factor of human resource competence built by educational background. There are some business actors who do not know the concept of journalizing transactions, even though this is the basis for preparing financial reports.